EFEKTIVITAS KINERJA APARATUR GAMPONG DALAM PELAYANAN PUBLIK DI GAMPONG BUMI SARI KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Amril, Yusri; Husna, Cut Asmaul (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
The purpose of this study was to determine the effectiveness of Gampong apparatus performance in public services. Besides that, by doing this research, the writer can find out the causes of ineffective public service activities in the keuchik's office. In writing this article used a qualitative method with a descriptive approach in the form of observation and interviews with informants. Informants for this study were Gampong Bumi Sari officials including service managers, keuchik and the community. In this study, interviews, observations, and documentation were used to collect data. The results of this study indicate that the level of effectiveness of Gampong apparatus performance in public services in Gampong Bumi Sari has not been effective, such as the absence of timeliness in providing services, the lack of quality human resources, the absence of service productivity, the level of service quality which is still lacking, the lack of responsiveness in services . Obstacles to the performance of Gampong apparatus in administering public services, namely Gampong apparatus have not carried out service innovations, infrastructure factors, limited network access, lack of community participation in supervising the performance of Gampong apparatus. It was concluded that the Gampong Bumi Sari apparatus was already responsible for its performance in accordance with the established rules and procedures, but in this case the implementation was still not optimal, for example Gampong apparatus were often late for work and did not arrive on time, and there were still Gampong apparatus who did not understand what their duties were. and the positions assigned.AbstraksiTujuan penelitian ini adalah untuk mengetahui efektivitas kinerja aparatur Gampong dalam pelayanan publik. Selain itu dengan dilakukannya penelitian ini maka penulis dapat mengetahui penyebab aktivitas pelayanan publik di kantor keuchik tidak efektif. Dalam penulisan artikel ini digunakan metode kualitatif dengan pendekatan deskriptif berupa observasi dan wawancara dengan informan. Informan untuk penelitian ini adalah aparatur Gampong Bumi Sari meliputi pengelolah pelayanan, keuchik dan masyarakat. Dalam penelitian ini, wawancara, observasi, dan dokumentasi digunakan untuk mengumpulkan data. Hasil penelitian ini menunjukkan tingkat efektivitas kinerja aparatur Gampong dalam pelayanan publik di Gampong Bumi Sari belum efektif, seperti belum adanya ketepatan waktu dalam memberikan pelayanan, minimnya kualitas sumberdaya manusia, belum adanya produktivitas pelayanan, tingkat kualitas layanan yang masih kurang, kurangnya daya tanggap dalam pelayanan. Kendala kinerja aparatur Gampong dalam penyelenggaraan pelayanan publik yaitu aparatur Gampong belum melakukan inovasi pelayanan, faktor infrastruktur, terbatasnya akses jaringan, kurangnya tingkat partisipasi masyarakat mengawasi kinerja aparatur Gampong. Disimpulkan bahwa aparatur Gampong Bumi Sari sudah bertanggungjawab terhadap kinerjanya sesuai dengan aturan dan prosedur yang ditetapakan, namun dalam hal ini pelaksanaannya masih belum optimal, seperti aparatur Gampong sering terlambat masuk kerja dan tidak datang tepat waktu, dan masih ada aparatur Gampong yang tidak mengerti apa tugasnya dan jabatan yang diberikan.